STUDI LITERATUR: SENAM KAKI MENINGKATKAN KEKUATAN OTOT INSTRINSIK KAKI PADA PENDERITA DIABETES MELLITUS TIPE II - Zahra Sativani; Dewi Fatimah Zahra; Ahmad Syakib (Ikatan Fisioterapi Indonesia cabang kota bekasi, 2021)
Background: Diabetes Mellitus type 2 has become one of the highest non-communicable diseases in Indonesia. The enhancement of the diseases almost happens every year. Metabolism changes lead to complications in the neurology system such as neuropathy. One of the causes of peripheral neuropathy is motor nerve damage that has an impact on intrinsic foot muscle weakness and it causes balance disorder in the sufferer. There need exercises to increase the intrinsic foot muscle strength through foot exercises. Objective: This study aims to investigate the effect of foot exercise on increasing the intrinsic foot muscle strength in diabetes mellitus type 2. Methods: This was a literature study method with the last 10 years of publication. Literature was obtained from 4 international online databases Pubmed, Semantic Scholar, Science Direct, and ProQuest. From a total of 567 pieces of literature, there was 8 literature relevant to this literature study. Result: From 8 literature shows that foot exercises have an effect on increasing the intrinsic muscle strength of the foot in people with Diabetes Mellitus type 2 seen from the p-value < 0,0005. Conclusion: Foot exercise is effective for increasing intrinsic foot muscle strength in Diabetes Mellitus type 2.